The Effectiveness of the Application of the Institutional Flow Report System (Silabi) in the Working Unit Development of Settlement Area Gorontalo Province - Frolawati Nggule; Muh. Firyal Akbar; Nur Eng Mokodompit (Journal of Management and Administration Provision, 2021)
This study aims to obtain information about the effectiveness of the application of the treasurer report system agency (SILABI) in the environment of the Gorontalo Province residential development area. The research method uses descriptive type with a qualitative approach. Data collection techniques were carried out through interviews with a number of informants and observations and recording secondary data related to the research problem. The results of the study concluded that the application of the agency treasury report system (SILABI) within the working area of the Gorontalo Province residential development area was not optimal due to the network in the application of this system which was not yet stable so that there were often delays in reporting, in addition to the ineffective management due to the available resources who do not understand and are familiar with the SILABI system.